Mitochondrial Myopathy and Congenital Cataract - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The autosomal recessive syndrome characterized by mitochondrial myopathy of cardiac and skeletal muscle, congenital cataract and lactic acidosis is described in two forms following a retrospective study of 16 patients at the University of Nijmegen, The Netherlands.